Systematics of the Southern African larks (alaudidae) : syringeal and vocalisation perspective - Nthangeni, Aluwani (My University, 2021)
The larks (Passeriformes, Passeri, Alaudidae) are small to medium-sized (10-23 cm) birds that are primarily terrestrial and cryptically plumaged hence they are difficult to encounter and recognise. The current taxonomic circumscription places these birds in a group that is comprised of 21 genera and 98 species, with all the genera occurring in Africa, 13 in Eurasia, and a single genus occurs in Australia and the Americas. Up until Alström et al. (2013), morphologically, the lark family was distinguished by having two unique and primitive features: i) the tarsus morphology (latiplantar and scutellate) consisting of the flat posterior surface covered with prominent scales, instead of being narrow and smooth as in other families, and ii) the syrinx (voice-generating organ). Despite that the structure of the syrinx of larks has been studied, literature reveals confusion pertaining to either the presence or absence of the pessulus, its level of development and size. To date, the work in Alström et al. (2013) remains the most comprehensive multi-locus phylogeny of the larks in which three strongly supported major clades (clade A – hereafter the Alaudid, clade B – the Mirafrid, clade C – the Ammomanid) emerged though with some uncertainty in some parts of the tree. In this study, the aim was to investigate the utility of syringeal and vocal characters in classifying the species of larks, finding out how syringeal and vocal characters evolved and identifying characters that define clades. The gross morphology and histology of the syringes and song strophes of larks and their putative outgroups were studied. Gross morphologically and histologically, the larks were found to possess a typical syrinx classified as a ‘syrinx tracheo-bronchialis’ and pessulus was observed in larks and the outgroups studied. There were differences observed in the syringeal gross morphological structure across all the three major clades (A, B and C). This is with regard to the presence or absence of the divided or double bronchial rings variably observed in clade A, B and C. In clade B and C, the ossification is variably restricted to the centre of bronchial rings forming a serial pattern while in clade A, bronchial rings are variably almost fully ossified without forming any serial pattern. The prominent oblique muscle-like structure runs ventrally and it was only observed in clade C in Chersomanes albofasciata. On the other hand, the syringeal histology revealed differences in the shape of the pessulus (blunt, pointy or sharp), the pessulus position relative to bronchial rings 1, 2 and 3 (B1, B2 and B3 respectively), length of the internal tympaniform membranes and connective tissue along the internal tympaniform membrane. The position of the pessulus was variably found to align with B2, to be below B2 and to be positioned beyond B2. One-way Anova clearly showed that among the three clades (A, B and C) identified in Alström et al. (2013), a statistically highly significant difference (P < 0.01) was found between the song strophes of species in clade C and A. The species in clade A generally give song strophes defined by high maximum frequency, high peak frequency and broad bandwidth frequency. The species in clade B have a similar trend with those in clade A, possibly explaining the overlap between these clades and the statistically significantly difference between clade A and C. These findings may be in support of the phylogenetic findings in Alström et al. (2013) and this study wherein clade A and B shared a sister relationship while clade C was placed basally. Clade C, on the other hand, comprises song strophes that are defined by low maximum frequency, lower peak frequency and narrow bandwidth frequency and this clade differed significantly from clade A. Despite that not all of the species could be correctly classified to their respective clades based on the Discriminant Function Analysis’ partition plot, the largest number of correct classifications were for clade A (70%). In addition, the distinction among the clades was also observed in either the presence or the absence of wing clappings in the song strophes, either being detached from or attached to the song strophes. Clade B is the only one which was marked by the presence of wing clappings particularly, genus Mirafra, although they are reported in Chersophilus duponti which belongs to clade A but not included in this study. With regard to the vocal phylogeny, the topology was highly unresolved, and no relationships could be inferred. The tracing of the evolution of characters of eight vocal and five syringeal characters revealed that among the 13 characters for which the ancestral state reconstructions were performed, 12 are polymorphic that is, they underwent multiple state changes ranging from four to 18. Most character states were found to plesiomorphous and mainly leading to clades of which their ancestral nodes were defined largely by autapormorphic and symplesiomorphic states. These do not assist in explaining how the various characters evolved. In conclusion, the findings have shed some light concerning the general syringeal morphology and histological structures of larks, revealed that lark songs are not suitable for reconstructing the phylogeny, shed light on the evolution of the selected vocal and syringeal characters as well as identifying characters that define the three major clades of larks (the Alaudid, Mirafrid and the Ammomanid).
Thesis (M. Sc. (Zoology)) -- University of Limpopo, 2021
Keywords: Vocalisation; Alaudidae; Syringeal; Larks; Larks; Eremophila (Birds); Syrinx (Bird anatomy)